2018
DOI: 10.1093/mnras/sty134
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation inside atomic cooling haloes exposed to Lyman–Werner radiation

Abstract: Supermassive stars born in pristine environments in the early Universe hold the promise of being the seeds for the supermassive black holes observed as high redshift quasars shortly after the epoch of reionisation. H 2 suppression is thought to be crucial in order to negate normal Population III star formation and allow high accretion rates to drive the formation of supermassive stars. Only in the cases where vigorous fragmentation is avoided will a monolithic collapse be successful giving rise to a single mas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 81 publications
2
22
0
1
Order By: Relevance
“…Regardless of this, both approaches show similar values for the mass and accretion rates of the central object, which are also consistent with results from previous works (e.g. Regan & Haehnelt 2009;Latif et al 2013b,c;Shlosman et al 2016;Regan & Downes 2018a). Therefore, we do not expect this to change our conclusions significantly.…”
Section: Caveatssupporting
confidence: 93%
See 1 more Smart Citation
“…Regardless of this, both approaches show similar values for the mass and accretion rates of the central object, which are also consistent with results from previous works (e.g. Regan & Haehnelt 2009;Latif et al 2013b,c;Shlosman et al 2016;Regan & Downes 2018a). Therefore, we do not expect this to change our conclusions significantly.…”
Section: Caveatssupporting
confidence: 93%
“…For example, Regan & Haehnelt (2009) ;Latif et al (2013a); Choi et al (2015) used a pressure floor beyond a certain resolution level, which limited the maximum density to n H 10 6 − 10 12 cm −3 . Similarly, Latif et al (2013c); Shlosman et al (2016); Regan & Downes (2018a) employed sink particles that replace gas above a maximum density of n H 10 5 − 10 8 cm −3 . One disadvantage of these methods is the limited resolution in regions where density is highest, hence they only describe well the processes on large scales.…”
Section: Introductionmentioning
confidence: 99%
“…In this study we have used the publicly available adaptive mesh refinement code Enzo 2 to study the birth of a massive black hole seed from a SMS. We have utilised the SmartStar particles introduced in Regan & Downes (2018a) and augmented them with subgrid prescriptions specific to a black hole seed as we now discuss.…”
Section: Numerical Frameworkmentioning
confidence: 99%
“…The collapsing flow must also be prevented from forming the molecular hydrogen. Otherwise, the H 2 cooling can lead to fragmentation and formation of Pop III stars, thus preventing formation of a massive central black hole seed (Haiman et al 2000;Wise & Abel 2008;Begelman & Shlosman 2009;Regan & Haehnelt 2009;Greif et al 2011;Latif et al 2016;Regan & Downes 2018). Numerical simulations of an optically-thin collapse have confirmed that in the absence of a molecular cooling, the gas stays isothermal, at the atomic hydrogen cooling floor (Omukai 2001;Bromm & Loeb 2003;Shang et al 2010;Choi et al 2013Choi et al , 2015Latif et al 2013;Choi et al 2013;Latif et al 2016;Shlosman et al 2016).…”
Section: Introductionmentioning
confidence: 99%